Exploring the nitrogen ingestion of aphids--a new method using electrical penetration graph and (15)N labelling. - Franziska Kuhlmann; Sebastian E W Opitz; Erich Inselsbacher; Ulrika Ganeteg; Torgny Näsholm; Velemir Ninkovic (PLoS ONE, 2013)
Studying plant-aphid interactions is challenging as aphid feeding is a complex process hidden in the plant tissue. Here we propose a combination of two well established methods to study nutrient acquisition by aphids focusing on the uptake of isotopically labelled nitrogen ((15)N). We combined the Electrical Penetration Graph (EPG) technique that allows detailed recording of aphid feeding behaviour and stable isotope ratio mass spectrometry (IRMS) to precisely measure the uptake of nitrogen. Bird cherry-oat aphids Rhopalosiphum padi L. (Hemiptera, Aphididae) fed for 24 h on barley plants (Hordeum vulgare L., cultivar Lina, Poaceae) that were cultivated with a (15)N enriched nutrient solution. The time aphids fed in the phloem was strongly positive correlated with their (15)N uptake. All other single behavioural phases were not correlated with (15)N enrichment in the aphids, which corroborates their classification as non-feeding EPG phases. In addition, phloem-feeding and (15)N enrichment of aphids was divided into two groups. One group spent only short time in the phloem phase and was unsuccessful in nitrogen acquisition, while the other group displayed longer phloem-feeding phases and was successful in nitrogen acquisition. This suggests that several factors such as the right feeding site, time span of feeding and individual conditions play a role for the aphids to acquire nutrients successfully. The power of this combination of methods for studying plant-aphid interactions is discussed.